A Whisper of True Learning (LEARNing Landscapes, 2014)
In this article, I describe my journey to develop my Indigenous teacher identity, and I explore constructs that either diminished or enhanced my identity development within the experiences of formal and non-formal learning. I narrate a pivotal moment in my teaching career that made me question what kind of teacher I was going to be. It was a "whisper of true learning" that awakened the depths of my nêhiyâw identity. It made me realize that I had forgotten who I was and, at the same time, that it was my responsibility to remember where I came from for the benefit of my students.
Keywords: indigeneous; teacher; identity; formal learning; informal learning